Het boek Openbaring: De macht van Gods geduld - Decock, Paul Bernard (HTS teologiese studies, 2012)
The Apocalypse of John: The power of God's patience. John B. Thompson relates power primarily to institutions, which embody the aims of a specific social structure. However, human actions will either endorse this social structure and empower its institutions or undermine them. The Apocalypse of John attempts to use its prophetic authority to undermine the power of the institutions of the Roman Empire and of its social structure by challenging the communities to withdraw their support from these and to continue this project in their own prophetic mission to all nations. The Apocalypse challenges the symbolic universe of the Roman Empire (an important element in their social structure) and the power of its institutions with an alternative symbolic universe rooted in the Old Testament traditions of God as the creator. In this symbolic universe the throne of God with God’s judgement is the institution where true power is situated and which will bring the work of creation to its fulfilment. The Empire is revealed as embodying the aims of Satan, who alienates people from God and so destroys God’s creation. The communities are called upon to act according to the aims inspired by the alternative symbolic universe as lived out by Jesus (hence the emphasis on the ‘works’ and the reminder to ’persevere in doing the works of Jesus‘[2:26]). The power of God’s judgement is not yet fully experienced because in God’s patience it is delayed in order to give the opportunity to the communities and all nations to bring their ‘works’ in tune with the aims of creation and so to undermine and ‘overcome’ the power of the Empire and Satan. God’s imminent judgement is meant as the vibrant guarantee of the success of creation, of the value of the ‘works of Jesus’ and of the uselessness of the ‘works of Satan’. Although the faithful may appear as powerless victims they are in fact ‘agents’ of God’s creation.